Fair Pay and a Wagebill Argument for Wage Rigidity and Excessive Employment Variability - Jonathan Thomas (Center for Economic Studies and ifo Institute (CESifo), 2000)
This paper considers a two-period optimal contracting model in which firms make new hires in the second period subject to the constraint that they cannot pay discriminate either against or in favour of the new hires. Under an assumption on the information available to workers, it is shown that wages are less flexible than needed for efficient employment levels, with the result that too few hires are made in bad states of the world. Unemployment is involuntary. In an extension to the model, there may also be involuntary and excessive layoffs in some states of the world.
Keywords: 330; Implicit contract theory; wage rigidity; involuntary unemployment